CHITOSAN-BASE COAGULANTS IN COAGULATION-FLOCCULATION OF KAOLIN SUSPENSION - Bambang Piluharto; Mufrihah Nurhayati; Asnawati Asnawati (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2018)
Coagulation-flocculation is one of the waste water treatments using coagulant/flocculants agent. Using coagulant/flocculants based on natural polymers were many used due to many available, renewable source, and environment friendly. One of that coagulant/flocculants was chitosan that can be produced through deacetylation of chitin. Amino groups in the chitosan structure play important role in the coagulant/flocculants process. The aim of research is using chitosan-based coagulants in the coagulation-flocculation of kaolin suspension. In here, there were two coagulants type, first, single coagulant which chitosan with different molecular weight added alone in kaolin suspension. Second, mix coagulants which chitosan aid with alum in kaolin suspension. As the result, functional group analysis showed that chitosan with different molecular weight have the same functional groups. Increasing molecular weight of chitosan increase NH2 groups and degree of deacetylation. The removing turbidity of kaolin suspension showed that increasing molecular weight chitosan increase removing turbidity of kaolin suspension. Using double coagulant (chitosan and tawas) have the removing turbidity greater than single coagulant.